Mechanisms of Financial Support for Small Businesses and Their Effectiveness (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The effective functioning of financing mechanisms is of great importance for the sustainable development of small business and private entrepreneurship. Therefore, the analysis of existing financing instruments, the assessment of their effectiveness, and the search for ways to improve them are urgent tasks.